👤

What is the Simplify (32y)²



I need helpm ..​


Sagot :

Answer:

(8y-7)*(4y-3)

Step-by-step explanation:

Step-1 : Multiply the coefficient of the first term by the constant 32 • 21 = 672

Step-2 : Find two factors of 672 whose sum equals the coefficient of the middle term, which is -52 .

-672 + -1 = -673

-336 + -2 = -338

-224 + -3 = -227

-168 + -4 = -172

-112 + -6 = -118

-96 + -7 = -103

-84 + -8 = -92

-56 + -12 = -68

-48 + -14 = -62

-42 + -16 = -58

-32 + -21 = -53

hope it helps

PA BRAINLEAST PO